A PENGARUH TINGKAT PENGANGGURAN TERHADAP TINGKAT KEMISKINAN DI KABUPATEN BERAU - Amins, Dawami Buchori (PRODI EKONOMI PEMBANGUNAN, STIE MUHAMMADIYAH TANJUNG REDEB, 2017)
This research has the effect of unemployment rate on poverty level in Berau District. The local government of Berau Regency along with all related elements of society continuously strive to tackle the problem of poverty optimally. The results showed that unemployment rate had no significant effect on poverty level in Berau District. This means the research hypothesis that alleged unemployment rate significantly affects poverty level in Berau District is rejected. Although the effect of the unemployment rate on poverty rate is not significant but the pattern of the relationship is positive, it means that any decrease in unemployment rate will be able to decrease the poverty level in Berau district, on the contrary any increase of unemployment rate will increase poverty level, but the level of weak relationship indicated by correlation level r) of 0.310 or 31%